The Influence of the Webbed-type Integrated Model on Students' Critical Thinking Ability in Social Sciences Material in the Field of Sociology Studies in SHS - Lenggogeni, Putri; Ananda, Azwar; Fatimah, Siti (Postgraduate School, Universitas Negeri Padang, 2024)
The purpose of this research is to find out how the Webbed integrated learning paradigm influences the critical thinking abilities of Senior High School (SHS) students. This research was conducted using a one-group Pre-test-Post-test design in a pre-experimental setting. The research subjects were ten men and nine women who were class X students at SHS 12 Padang. The instruments used are test sheets and observation sheets. The critical thinking ability test consists of two stages, namely Pre-test and Post-test. Based on research, students' critical thinking skills obtained an average score of 87 on the Post-test and 71 on the Pre-test. A sig value of 0.251 < ? (0.05) was obtained using the Paired Sample T-test at ? (0.05) in data analysis SPSS 22 for Windows. Research findings show that the Pre-test and Post-test are significantly different. Apart from that, a medium category N-Gain value was obtained of 0.543. This shows that the use of the Webbed integrated learning model has an impact on student's critical thinking abilities both before and after treatment. Then in several aspects of critical thinking, such as argument evaluation and information analysis, women tend to show higher levels than men, with the average score for women's argument evaluation being 78% while men's is 72%. However, in other aspects such as information synthesis and making conclusions, men tend to stand out, with men's average information synthesis score being 80% while women's is 76%.